Implementasi Peranan Quantum Teaching Dalam Pembelajaran Bahasa Arab Kelas VII SMP Muhammadiyah Limbung Gowa Sulawesi Selatan - Rahmawati Rahmawati; Abd. Rahim Razaq; Muhammad Ibrahim (Universitas Muhammadiyah Makassar, 2021)
This study used a Quantum Teaching learning model, using classroom action research. the aim of this research is 1) To find out whether Arabic learning runs effectively when the Quantum Teaching learning model is applied and can be absorbed well. 2) To see whether students are increasingly interested in learning Arabic when the Quantum Teaching learning model is applied. 3) To find out what are the inhibiting and supporting factors for learning Arabic for the students of SMP Muhammadiyah Limbung. Regency. Gowa, South Sulawesi.The results of this study prove that the changes are quite good, and the students are more enthusiastic about learning after getting Arabic learning with the Quantum Teaching model, the students' interest in learning is getting better and the enthusiasm for learning is increasing so that learning can be considered quite effective. Some of the influences that arise are caused by the influence of technological advances, taking emotional approaches and actively establishing communication and then motivating students in need.